A new genus of monogenean parasites (Capsalidae: Benedeniinae) from stingrays Rajiformes: Dasyatidae) with a description of a new species from the long-tailed stingray Himantura uarnak Forsskål from Queensland, Australia - Whittington, I. D.; Barton, D. P. (Journal of Natural History, 1990)
Trimusculotrema warnaki gen. et sp. nov. is described from the skin of Himantura uarank Forsskål. Trimusculotrema is distinguished from other genera in the Benedeniinae by the following combination of anatomical features: accessory sclerites and anterior hamuli small; haptor with two or three intrinsic, concentric muscle bands; haptor papillate ventrally; cirrus sac with internal seminal vesicle and spermatophore matrix reservoir; separate male and female pores opening ventrally and dorsally respectively; vagina short. On the basis of these features Benedenia micracantha Euzet and Maillard, 1967 from the skin and B. leucanthemum Euzet and Maillard, 1967 from the gills of Dasyatis marmorata Steindachner off Senegal are transferred to the new genus as Trimusculotrema micracantha comb. nov. and T. leucanthemum comb. nov. The presence of haptoral papillae, noted previously in some species of Entobdella, perhaps indicates that the new genus is more closely related to entobdellids than to benedeniids. Several living specimens of T. uarnaki had 7 (2–17) eggs in early cleavage projecting from the body, their appendages gripped in a muscular sphincter at the uterine opening. These egg bundles appear to be shed from the parasite soon after laying.
Revision to Benedenia, erection of Trimusculotrema Revision to Benedenia, erection of Trimusculotrema